Anxiety, Uncertainty, and Resilience During the Pandemic Period - Anthropological and Psychological Perspectives 2021
DOI: 10.5772/intechopen.97798
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Issues during Covid-19 Pandemic in Portuguese Prisons

Abstract: During imprisonment, inmates face many difficulties to adapt to prison life well depicted in either classical works or recent research. They usually face many struggles related to the lack of contact with their families. For instance, the less the number of prison visits, the higher levels of aggressiveness and, consequently, the lower levels of adaptation. Additionally, this population is already problematic in “normal conditions” of their imprisonment. When facing crisis – such as the Covid-19 pandemic – the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These initiatives must be multifaceted, integrating efforts to safeguard and enhance mental health with activities to manage other mental illnesses [ 62 ]. Second, when inmates enter the penal system and serve their sentences, they should be screened for mental health disorders on a regular basis [ 21 ]. Third, this study may help develop psychotherapeutic programs to evaluate how the incarcerated might best cope with stress and manage emotions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These initiatives must be multifaceted, integrating efforts to safeguard and enhance mental health with activities to manage other mental illnesses [ 62 ]. Second, when inmates enter the penal system and serve their sentences, they should be screened for mental health disorders on a regular basis [ 21 ]. Third, this study may help develop psychotherapeutic programs to evaluate how the incarcerated might best cope with stress and manage emotions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the pooled prevalence of mental illness in prisons, treatment barriers appear to increase the poor response to this problem. Indeed, past research has shown that incarceration creates specific mental health care challenges [ 21 ]. Often, these constraints begin with the arrival of prisoners, who are often reluctant to seek aid on their own.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations